2014
DOI: 10.1002/lt.23832
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of preoperative and intraoperative liver biopsies for evaluating donor steatosis in living related liver transplantation

Abstract: The role of liver biopsy in selecting optimal donors is an area of continuing controversy in living donor liver transplantation (LDLT). Our aim was to assess the potential implications of preoperative and intraoperative biopsies for evaluating donor liver fat content. Three thousand eight hundred fifty-nine consecutive subjects underwent predonation needle biopsy of the right lobe, and 1766 of these subjects actually donated their livers for LDLT and underwent intraoperative wedge biopsies of paired right and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…If we also consider our results, there seems to be accumulating evidence that even healthy, non‐obese subjects could be candidates for NAFLD screening and monitoring in the future, particularly if they have a certain risk factor such as high visceral adiposity. If our findings are borne out in further studies including cost‐effectiveness analysis, adding a single‐slice unenhanced CT scan to routine health‐check programs for dyslipidemic patients may be of potential benefit, given the suboptimal performance of ultrasonographic study, even in detecting cases of severe fat infiltration of liver . This concept was previously supported by van der Poorten et al ., who reported that visceral fat was directly associated with NASH and fibrosis in NAFLD patients .…”
Section: Discussionmentioning
confidence: 54%
“…If we also consider our results, there seems to be accumulating evidence that even healthy, non‐obese subjects could be candidates for NAFLD screening and monitoring in the future, particularly if they have a certain risk factor such as high visceral adiposity. If our findings are borne out in further studies including cost‐effectiveness analysis, adding a single‐slice unenhanced CT scan to routine health‐check programs for dyslipidemic patients may be of potential benefit, given the suboptimal performance of ultrasonographic study, even in detecting cases of severe fat infiltration of liver . This concept was previously supported by van der Poorten et al ., who reported that visceral fat was directly associated with NASH and fibrosis in NAFLD patients .…”
Section: Discussionmentioning
confidence: 54%
“…Some centers perform routine liver biopsy for all potential donors, while other centres only perform liver biopsy in selected high risk donors (older age, comorbidities, abnormal liver function tests). Assessment of steatosis through visual inspection of the graft has a positive predictive value of less than 20% for mild steatosis and only 70% for severe steatosis [58]. Surrogate markers of steatosis, like liver ultrasound coexisting with normal transaminases have also been proposed.…”
Section: Before Liver Transplantationmentioning
confidence: 99%
“…Previously in our center, liver quality was assessed based on liver biopsy which was performed when moderate or severe fatty change was suspected in sonography or CT image and donors with <30% macrovesicular steatosis were accepted. However, since 2010, MRS and/or MR chemical shifting technique (especially in cases with heterogenous fatty distribution) has been routinely performed to evaluate the degree of fatty change with its good correlation . At present, we cautiously accept donors considering other factors together if fat fraction was >10%.…”
Section: Discussionmentioning
confidence: 99%